A survey of radiation level in Singapore - Chua, Zong Gen. (2012)
Radiation has come to a public awareness after the leakage of nuclear radiation from the failure of nuclear reactors in Japan at Fukushima. Not only are the Japanese concerned about the leakage of the nuclear radiation, so does Singaporean even though Singapore is 5700 km away from the disaster area.